New PTEN mutation identified in a patient with rare bilateral choroidal ganglioneuroma - Jiang, Zhaoxin; Zhang, Ting; Chen, Chonglin; Sun, Limei; Li, Songshan; Ding, Xiaoyan (BMC ophthalmology, 2020)
Background Choroidal ganglioneuroma is an extremely rare tumor, and there is little knowledge regarding its pathogenesis. We aimed to investigate the phenotypic and genetic alterations in one sporadic patient with a rare case of bilateral choroidal ganglioneuroma. Methods A 6-year-old boy with histological diagnosis of bilateral ganglioneuroma was recruited for the study. Comprehensive ophthalmic examinations were performed. Genomic DNA was extracted from the peripheral blood samples collected from the patient, his unaffected family members, and 200 unrelated control subjects from the same population. Whole exome sequencing was performed and raw reads were aligned to the human genome reference (hg19) using Burrows-Wheeler Aligner. DNA from all available family members was Sanger sequenced for segregation analysis. Results Extensive bilateral retinal detachments were observed via optical coherence tomography. Diffuse thickening of choroid was identified with ultrasound B scan and magnetic resonance imaging. Genetic analysis revealed the presence of a novel heterozygous PTEN frameshift mutation, c.498delA (p.Thr167LeufsTer16), in exon 6. It was present in the affected individual, but not in any of the family members. Genetic analysis revealed that there was no mutation in neurofibromatosis-related genes in the family. Upon performing comprehensive systemic examinations, no obvious abnormalities in other organs were observed. Conclusions A novel de novo PTEN mutation was identified in a patient with bilateral choroidal ganglioneuroma. Although PTEN mutations are known to induce multiple abnormalities, choroidal ganglioneuroma can be the first manifestation without abnormalities in other organs. Further studies are needed to confirm the association between choroidal ganglioneuroma and PTEN mutation.